Certifying the cause of death: an audit of wording inaccuracies. - Slater, D N (1993)
AIMS: To audit wording and formulation inaccuracies in certifying the cause of death. METHODS: Five hundred causes of death were analysed from the counterfoils of medical death certificates (Form 66). Wording and formulation inaccuracies were defined as terms contrary to the notes given to doctors in books on death certificates. RESULTS: One or more inaccuracies were identified in 29% of cases. In 5.8% of cases, the inaccuracies were sufficiently serious to warrant further action or enquiry by the Registrar of Births and Deaths, including referral to Her Majesty's Coroner. CONCLUSIONS: Most inaccuracies could have been avoided by adhering to the notes for medical practitioners contained in books of death certificates. The wording and formulation of causes of death warrants special prominence in under-graduate and postgraduate medical education. The topic should be audited and medical practitioners should pay particular attention to cases worthy of referral to HM Coroner.